Effect of EGR on a diesel engine fueled with waste plastic oil blend. Issue 1 (April 2021) - Balaji, G.; Anvar Saheel, I.; Hariharan, M.; Palaniappan, P. L.
Abstract: With the increasing global demand for fuels, there is a need to reduce vehicular emissions which are one of the major causes of air pollution around the globe. NOx emissions leads to health issues, acid rain, global warming, etc. Diesel engines are the major sources for NOx emissions. Hence there is a need to reduce the emissions from the engines by means of alternate fuels and emission control technologies. This investigation deals with the effect of exhaust gas recirculation (EGR) on single cylinder, direct injection diesel engine using plastic oil and diesel blend (10% plastic oil + 90% diesel) at EGR rates of 5%, 10% and 15%. Plastic oil blends were able to operate in diesel engines without any modifications and based on the results, EGR decreases the NOx emissions with a minimum increase in specific fuel consumption. The engine with the EGR rate of 15% and at the full load condition, the emission level of NOx has been decreased from 1327 to 661 ppm. Hence it was concluded that the low emission level of NOx can be obtained using EGR for the plastic oil blend. The results showed that DPB+EGR15 blend had the least NOx emission.